Modern Japanese political thought and international relations - Rösch, Felix; Watanabe, Atsuko, 1968- (Global dialogues : developing non-Eurocentric IR and IPE, 2018)
"First book-length investigation of modern Japanese political thought and IR with a focus on non-western and indigenous Asian practices of IR"--